Functional asymmetry and essential structural roles of PDE6α and PDE6β subunits in rod–photoreceptor integrity - Roman Smidak; Deepak Poria; Fangyuan Gao; Zhiqian Dong; Jianye Zhang; Marco Bassetto; Eleonora Risaliti; Aleksander Tworak; Weijing Liu; Vladimir J. Kefalov; Krzysztof Palczewski (Proceedings of the National Academy of Sciences, 2026)
Tetrameric rod phosphodiesterase-6 (PDE6), comprised of an α/β heterodimeric catalytic core and two inhibitory γ subunits, critically regulates cyclic GMP (cGMP) levels in rod photoreceptors. While the rod-PDE6 catalytic core is a heterodimer, the cone isoform is an α′/α′ homodimer. This structural difference suggests a unique role for each rod subunit. Due to the lack of heterologous expression systems, we generated four transgenic mouse models to examine the functional contributions of the N-terminal pony-tail (Pt)-motifs and of the catalytic domains of the individual catalytic subunits of rod PDE6 in vivo. We generated two N-terminal deletions (PDE6αΔ2-48AA and PDE6βΔ2-46AA); and two active-site mutations (PDE6αH599A and PDE6βH597A) designed to selectively abolish catalytic activity. Native mass spectrometric analysis of heterozygous mice revealed that only wild-type enzyme was produced. While homozygous mutations in all lines caused complete photoreceptor degeneration, analysis of heterozygous lines revealed a disproportionately greater impact of β-subunit mutations on protein stability, enzymatic activity, and visual function. These findings establish that both active subunits are essential for rod integrity, but a significant functional asymmetry exists within the PDE6αβ heterodimer. Our results demonstrate that the PDE6β subunit plays a more dominant role in maintaining the structural and functional pool of PDE6 enzyme.